Capacity Development of Local Service Organizations Through Regional Innovation in Papua, Indonesia After the COVID-19 Pandemic - Prasetyo, Andjar; Gartika, Dewi; Hartopo, Agustinus; Harwijayanti, Bekti Putri; Sukamsi, Sukamsi; Fahlevi, M. (Frontiers in Psychology, 2022)
This study aims to identify and describe the regional innovations produced in Keerom Regency, Papua Province, Indonesia after the COVID-19 Pandemic, to analyze integrated regional service capacity indicators with a special focus on organizational performance indicators in integrated units that can be measured quantitatively and simply. In addition, to create an understanding of organizational performance in geographic areas. The method approach uses a mixed-methods description to tell the results of the study. . Secondary data was analyzed in the form of innovation proposals for as many as 108 regional innovations. The analysis used adopts local service capacity which was developed with additional indicators of innovation. Local Service Indicators used to consist of Leadership and Governance; Structure and System; Human Resources; Financial management; Program Management; Monitoring and Evaluation Plan; Partnerships, External Relations and Networks; Knowledge Management; and organizational innovation. Local services are built using spreadsheet tools to make the process easier to use. The result is that organizational services in regional innovation as a whole still reach a score of 52% on a 100% scale giving the result that organizational services have been carried out amid the limitations of local governments which are characterized by limited knowledge needed, not yet optimally prepared programs, low organizational acceleration. for regional innovation, the harmonization process between planning evaluation, and monitoring is not yet optimal.